ANALISIS HAK-HAK ISTRI NUSYUZ PASCA PERCERAIAN - Inayah Anugerah Ulfatunnisa; Asni; Fatimah, Siti Nurul (Universitas Islam Negeri Alauddin Makassar, 2025)
This study discusses the analysis of the rights of nusyuz wives after divorce in the decisions of the Class IA Watampone Religious Court (case study of Decision Number 957/Pdt.G/2021/PA.Wtp). Therefore, finally the author explores how the description of the divorce case due to Nusyuz's wife and the legal considerations for the judge in the Watampone Religious Court Decision Number 957 Pdt.G/2021/Pa.Wtp. This type of empirical legal research, sources of data in the field such as observations and interviews. The results of this study reveal that based on the results of the research, in the Compilation of Islamic Law article 80 paragraph (7) which states that the husband's obligations as referred to in paragraph (5) fall if the wife is proven nusyuz. In this case the plaintiff is considered nusyuz so that the plaintiff does not get iddah and madhiyah living but still gets mut'ah (consolation money). marriage with kindness or release (divorce).